The Biomechanics Analysis: Development of Biomechanics Analysis Algorithm With OpenPose Motion Capture System - Chan Yung Wai,; Mohd Zamani Bin Ngali, (Research Progress in Mechanical and Manufacturing Engineering, 2022)
This research is about to develop a biomechanics analysis algorithm to do quantitative biomechanics analysis on the movement of a person. This research is conducted because the analysis done by the coaches to their athletes is a qualitative analysis. This kind of analysis may not be understood clearly by a non-experts. The objective of this research is to retrieve motion captured data from OpenPose open source code, to develop biomechanics analysis algorithm from the captured data and to perform distance, velocity, acceleration and angular biomechanics analysis with developed algorithm. The motion capture in this research will be performed by using OpenPose Demo. The coordinate data of the keypoints analysed by using OpenPose Demo is only x and y axes which refer to the pixels of the screen and the origin is the right bottom corner of the screen. This also means that the coordinate data of the keypoints is in 2 dimensiona (2D). The obtained 2D coordinate of keypoints will be analysed by the developed biomechanics analysis algorithm to obtained angle, distance travelled, velocity and acceleration of the keypoints. The algorithm developed is for biomechanics analysis. The biomechanics analysis algorithm only analyses kinematic such as velocity and acceleration and displacement and angle. In this research, the source code of the OpenPose Demo is first downloaded from GitHub and installed into laptop. OpenPose Demo is used to do motion capturing and collecting data of the keypoints of the body. The MatLab is also installed for developing an algorithm for retrieving coordinate data from the data of motion captured and it is also used to develop algorithm for biomechanics analysis. Then, the developed algorithm will be tested. The angle analysed by using the developed biomechanics analysis algorithm is smooth. However, the displacement, velocity and acceleration analysed by using the developed biomechanics analysis algorithm are fluctuating. The results of the displacement, velocity and acceleration is fluctuating because of the inconsistent of the frame per second (fps) of the OpenPose Demo. Furthermore, the coordinate of the keypoints analysed by OpenPose Demo is 2 dimensional coordinate and the pixels are the reference of the coordinate. Hence, OpenPose Demo required to be replaced by a more advanced motion captured system in order to collect more accurate motion data.